THE ROLE OF ENDOTHELIAL DYSFUNCTION IN THE FORMATION OF COMPLICATIONS OF DIABETES MELLITUS AND THE PROSPECTS FOR ITS CORRECTION BY THE RECEPTOR ANTAGONIST INTERLEUKIN-1 - E. V. Suprun; S. V. Tereshenko (Vіsnik Naukovih Doslіdžen', 2017)
Diabetes mellitus (DM) is a steadily progressing disease that affects mainly people of working age and quickly leads to the development of systemic complications. DM takes the third place in the mortality statistics after cardiovascular and oncological diseases. The main cause of disability and mortality in diabetes are micro- and macrovascular complications, leading to the development of cardiovascular and cerebrovascular diseases. Diabetes is associated with an increased risk of developing myocardial infarction and ischemic stroke and with their less favorable outcome.